COPYRIGHT DAN RIGHT TO COPY (PEMAHAMAN DASAR HAK CIPTA DAN HAK YANG TERKAIT DENGAN HAK CIPTA DALAM BIDANG HAK KEKAYAAN INTELEKTUAL) - Samuel Dharma Putra Nainggolan; Ni Made Yordha Ayu Astiti; Diajeng Woro Andini (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
Copyright is a system of rights in the field of Intellectual Property Rights (IPR). In Indonesia, arrangements regarding Copyright are currently governed by Law Number 28 of 2014 Concerning Copyright. Regulates the scope and protection of a work which is the embodiment of human creativity, taste and initiative as God's creatures. Copyright which is an exclusive right attached to the Author in which there are Economic Rights and Moral Rights. Authors and other parties who receive Rights Related to Copyrights can receive economic benefits from an existing copyrighted work (Economic Rights). died (moral rights). In the Civil Law System legal system, the focus is on protection of the Author, whereas in the Common Law System legal system, the focus is on the protection of Works.